Javanese Islam: The Flow of Creed - Jamhari Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
In this article, popular Islam meaning Islam that is practiced and interpreted in accordance with local context is considered to be